A review of new vibration issues due to non-ideal energy sources - Balthazar, José Manoel [UNESP]; Brasil, RMLRF; Fenili, A.; Belato, D.; Felix, JLP; Garzelli, F. J. (Chapman & Hall/crc Press, 2004)
We analyze the dynamical coupling between energy sources and structural response that must not be ignored in real engineering problems, since real motors have limited output power. We present models of certain problems that render descriptions that are closer to real situations encountered in practice.